Yemen, Saudi-led military intervention and international law - Eishan Jan, Mohammad Naqib; Lawan Haruna, Abdulrashid (Faculty of Law, Accountancy and International Relations, UniSZA, 2015)
On 25 March 2015, Saudi Arabia launched a military intervention, known as “Operation Decisive Storm”, in civil war stricken Yemen changing the status of the conflict from ‘non-international armed conflict’ (NIAC) to ‘international armed conflict’ (IAC). Saudi Arabia conducted the operation in response to de jury Yemeni government request, headed by President Abd Rabb Mansur Hadi, and in coordination with a coalition comprising the United Arab Emirates, Qatar, Kuwait, Bahrain, Jordan, Morocco, Sudan, Pakistan and Egypt. The United States is on the side of the coalition providing ‘logistical and intelligence support’. The de facto Yemeni government is led by Abdul Malik al-Houthi (a Zaidi Shia Muslim) and former president Ali Abdullah Saleh (a Sunni Muslim). The de facto government is supported by Iran. Some observers describe the war in Yemen as a proxy war fought on behalf of Iran and Saudi government and the victims of the war are the poor and innocent people of Yemen. The conflict in Yemen raises numerous questions that this paper attempt to answer. Does the Operation Decisive Storm a lawful use of force? Is Iran’s support to Houthi- led de facto government lawful? Is this conflict an international armed conflict or a non-international armed conflict? Does international humanitarian law (IHL) applies to the conflict in Yemen and if so do the parties to the conflict abide by their obligation under international law? These questions will be discussed in this paper with reference to the relevant international law provisions using the primary sources as well as the subsidiary sources of the law.